Gabapentin‐induced pharmacodynamic effects in the spinal nerve ligation model of neuropathic pain. (16th July 2013) - Hooker, B.A.; Tobon, G.; Baker, S.J.; Zhu, C.; Hesterman, J.; Schmidt, K.; Rajagovindan, R.; Chandran, P.; Joshi, S.K.; Bannon, A.W.; Hoppin, J.; Beaver, J.; et al.
Abstract Background The function of brain networks can be changed in a maladaptive manner in response to chronic neuropathic pain. Analgesics can reduce pain by acting on such networks via direct or indirect (peripheral or spinal) mechanisms. This investigation aimed to map gabapentin's pharmacodynamics (PD) in the rodent brain following induction of neuropathic pain in order to further understand its PD profile. Methods Pharmacological magnetic resonance imaging (phMRI) and a novel functional connectivity analysis procedure were performed following vehicle or gabapentin treatment in the rat spinal nerve ligation (SNL) model of neuropathic pain as well as sham animals. Results phMRI performed in SNL animals revealed robust gabapentin‐induced responses throughout the hippocampal formation, yet significant (p < 0.05, corrected for multiple comparisons) responses were also measured in other limbic structures and the sensorimotor system. In comparison, sham animals displayed weaker and less widespread phMRI signal changes subsequent to gabapentin treatment. Next, communities of networks possessing strong functional connectivity were elucidated in vehicle‐treated SNL and sham animals. We observed that SNL and sham animals possessed distinct functional connectivity signatures. When measuring how gabapentin altered the behaviour of the discovered networks, a decrease in functional connectivity driven by gabapentin was not only observed, but the magnitude of this PD effect was greater in SNL animals. Conclusions Using phMRI and functional connectivity analysis approaches, the PD effects of gabapentin in a preclinical neuropathic pain state were characterized. Furthermore, the current results offer insights on which brain systems gabapentin directly or indirectly acts upon.